Moderatisme Politik Islam Indonesia Era Soekarno: Studi Resolusi konflik Indonesia – Malaysia - Sri Windari; Muhammad Ilham Aziz (Historia Madania: Jurnal Ilmu Sejarah, 2022)
This paper examines the agreement between Indonesia and Malaysia which is a form of moderate Islamic attitude shown by the parties or community organizations that played a role at that time. In this study, the authors used a qualitative descriptive research method. The data analysis technique used is the technique proposed by Miles and Huberman, which consists of data reduction, data presentation, and conclusions. The resolution of the conflict that occurred between Indonesia and Malaysia is also known as Konfrontasi or "Down with Malaysia", this occurred because of the conflict in the Sabah and Sarawak regions. This dispute is a stage of Islamic politics in Indonesia so that it has an impact on the moderate attitude of Islamic politics in Indonesia. the involvement of Islamic Community Organizations in the policies heralded by Soekarno became an internal crisis in the Islamic political conditions at that time. Organizations that are quite influential and involved are the Masyumi Party, the NU Party, and the Ansor Youth Movement. In enough conflict "G resolution of Malaysia" which finally resulted in a peaceful resolution between the two parties. With various agreements that occurred from 1963-1966 the agreement agreement for the Sabah and Sarawak regions to be included in the territory of Malaysia.Keywords: Islamic Political Moderatism, Conflict Resolution, Masyumi Party, NU Party, Ansor Youth Movement.